2011
DOI: 10.3389/fpsyg.2011.00088
|View full text |Cite
|
Sign up to set email alerts
|

Early ERP Modulation for Task-Irrelevant Subliminal Faces

Abstract: A number of investigations have reported that emotional faces can be processed subliminally, and that they give rise to specific patterns of brain activation in the absence of awareness. Recent event-related potential (ERP) studies have suggested that electrophysiological differences occur early in time (<200 ms) in response to backward-masked emotional faces. These findings have been taken as evidence of a rapid non-conscious pathway, which would allow threatening stimuli to be processed rapidly and subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 49 publications
6
54
2
Order By: Relevance
“…This means that we cannot infer from the discrimination threshold task that 10 ms is truly non-conscious for the processing of happy faces. However, recent ERP studies confirmed presentation times below 20 ms for non-conscious processing of happy faces (Balconi and Lucchiari 2008;Pegna et al 2011;Smith 2011). Therefore, it is conceivable to assume that presentation times of 10 ms as used in our ERP experiment are really non-conscious also for the processing of happy faces.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This means that we cannot infer from the discrimination threshold task that 10 ms is truly non-conscious for the processing of happy faces. However, recent ERP studies confirmed presentation times below 20 ms for non-conscious processing of happy faces (Balconi and Lucchiari 2008;Pegna et al 2011;Smith 2011). Therefore, it is conceivable to assume that presentation times of 10 ms as used in our ERP experiment are really non-conscious also for the processing of happy faces.…”
Section: Discussionmentioning
confidence: 68%
“…Recent studies used event-related potential (ERP) recording to investigate the time course of non-conscious and conscious emotional face processing (Pegna et al 2011;Smith 2011). Studies of ERPs generated by faces often focus on key components such as the P100 and the face-sensitive N170.…”
Section: Introductionmentioning
confidence: 99%
“…Several ERP studies have suggested that ERP components, such as N2/P3 recorded from a midline site, are enhanced more by subliminally presented fearful faces than by supraliminally presented fearful faces [14,[29][30][31][32][33]. Furthermore, Pegna et al [34] reported that subliminally presented fearful faces elicited larger N170 amplitudes than did supraliminally presentation of fearful faces. These findings indicate a double dissociation for subliminal versus supraliminal processing of fearful faces [32], raising the possibility that subliminally presented fearful face stimuli may affect the perception of subsequently presented supraliminal face stimuli via subcortical visual pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, electrophysiological studies using face stimuli have provided evidence that faces can be processed at an early stage and without awareness both in healthy controls (e.g., Kiss and Eimer, 2008 ; Pegna et al, 2008 , 2011 ) and in patients with cortical blindness ( Gonzalez Andino et al, 2009 ; Del Zotto et al, 2013 ). Using a backward masking paradigm in healthy participants, Kiss and Eimer (2008) found that both subliminal and supraliminal fearful faces produced an enhanced early frontal positivity compared to neutral faces between 140 and 180 ms post-stimulus.…”
Section: Introductionmentioning
confidence: 99%